Kinetics and product analysis of the reaction catalysed by recombinant homoaconitase from Thermus thermophilus - Jia, Yunhua (Portland Press Ltd., 2006)
HACN (homoaconitase) is a member of a family of [4Fe-4S] cluster-dependent enzymes that catalyse hydration/dehydration reactions. The best characterized example of this family is the ubiquitous ACN (aconitase), which catalyses the dehydration of citrate to cis-aconitate, and the subsequent hydration of cis-aconitate to isocitrate. HACN is an enzyme from the α-aminoadipate pathway of lysine biosynthesis, and has been identified in higher fungi and several archaea and one thermophilic species of bacteria, Thermus thermophilus. HACN catalyses the hydration of cis-homoaconitate to (2R,3S)-homoisocitrate, but the HACN-catalysed dehydration of (R)-homocitrate to cis-homoaconitate has not been observed in vitro. We have synthesized the substrates and putative substrates for this enzyme, and in the present study report the first steady-state kinetic data for recombinant HACN from T. thermophilus using a (2R,3S)-homoisocitrate dehydrogenase-coupled assay. We have also examined the products of the reaction using HPLC. We do not observe HACN-catalysed ‘homocitrate dehydratase’ activity; however, we have observed that ACN can catalyse the dehydration of (R)-homocitrate to cis-homoaconitate, but HACN is required for subsequent conversion of cis-homoaconitate into homoisocitrate. This suggests that the in vivo process for conversion of homocitrate into homoisocitrate requires two enzymes, in simile with the propionate utilization pathway from Escherichia coli. Surprisingly, HACN does not show any activity when cis-aconitate is substituted for the substrate, even though other enzymes from the α-aminoadipate pathway can accept analogous tricarboxylic acid-cycle substrates. The enzyme shows no apparent feedback inhibition by L-lysine.